VSM Reduces Lead Time in Fabrication Material Warehouse Operations: VSM Mengurangi Waktu Tunggu dalam Operasi Gudang Bahan Baku Manufaktur - Regan Fitra Ramadhan; Dira Ernawati; Isna Nugraha (Academia Open, 2026)
General Background Global competition has increased the strategic role of warehousing within supply chain management, particularly in supporting production reliability and logistics performance. Specific Background Fabrication material warehouses in engineering and construction companies often experience inefficiencies caused by non-value-added activities, excessive inventory, transportation constraints, and waiting time. Knowledge Gap Empirical studies that systematically integrate Value Stream Mapping, Process Activity Mapping, and the Waste Assessment Model to quantify and prioritize waste in fabrication material warehouses remain limited. Aims This study aims to identify dominant waste types and redesign warehouse activities using a lean warehousing approach at a fabrication material warehouse of PT XYZ. Results The current state analysis shows a total lead time of 891 minutes with 557 minutes of value-added time and 11 non-value-added activities. The future state Value Stream Mapping reduces lead time to 689 minutes, indicating a 23% improvement in warehouse activity performance through reduced delay and non-value-added processes. Novelty This study combines Value Stream Mapping, Process Activity Mapping, and the Waste Assessment Model to provide an integrated and structured waste identification framework for fabrication material warehousing. Implications The findings offer practical guidance for warehouse layout management, inventory control, and activity synchronization, supporting more efficient material flow and improved operational reliability in fabrication warehouse operations. Highlights: Non-value-added activities dominated delay and material handling processes within warehouse operations. Integrated mapping and waste analysis enabled measurable time reduction across storage and loading stages. Structured improvement recommendations supported better coordination of material flow and documentation processes. Keywords: Lean Warehousing, Process Activity Mapping, Waste Assessment Model, Fabrication